Effect of NACA 0010 airfoil car spoiler towards downforce and drag force / Muhammad Azraai Ahmad Fisal - Ahmad Fisal, Muhammad Azraai (2013)
This paper presents the analysis of downforce and drag force theory of a spoiler in MATLAB and DesignFOIL software. The observed car spoiler characteristic is an airfoil shape of NACA 0010 airfoil spoiler, 1.65m wingspan and 0.25m chord length. The analysis is tested by varies the speed of the vehicle and the angle of attack of the spoiler toward the air incident on the spoiler. The results obtained from the analysis were recorded in table and plotted on graph. Conceptual assumptions were verified as the down force increase to eliminate lift of the car, the drag is also increase that obeys the basic function of a spoiler.